2017
DOI: 10.1210/jc.2016-3845
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Suppression of Gonadotropins and Ovarian Hormones by Elagolix in Healthy Premenopausal Women

Abstract: Elagolix administration allows for modulation of gonadotropin and ovarian hormone concentrations, from partial suppression at lower doses to nearly full suppression at higher doses. The results of this study provide a rationale for elagolix dose selection for treatment of sex hormone-dependent diseases in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
116
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 20 publications
4
116
1
Order By: Relevance
“…25 Although women were instructed to use dual nonhormonal contraception, pregnancies were reported during the trials. There were no anomalous outcomes in the elagolix groups in these trials, but no conclusion on the effect of elagolix on pregnancy could be made, owing to the small number of pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Although women were instructed to use dual nonhormonal contraception, pregnancies were reported during the trials. There were no anomalous outcomes in the elagolix groups in these trials, but no conclusion on the effect of elagolix on pregnancy could be made, owing to the small number of pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Observed reductions in pain and reports of hypoestrogenic adverse events were consistent with the mechanism of action of elagolix, which competitively inhibits GnRH receptors in the pituitary gland and leads to a rapid reduction in circulating gonadotropins and estradiol. 25 This mechanism is different from that of GnRH agonists, which after an initial stimulatory phase desensitize GnRH receptors in the pituitary and subsequently cause depletion of pituitary gonadotropins and full suppression of estradiol to levels that are equivalent to those associated with bilateral oophorectomy. 33 Agonists are effective in reducing both dysmenorrhea and nonmenstrual pelvic pain in women with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a dose of 150 mg once daily, elagolix suppresses E2 to early follicular phase levels (approximately 50 pg/mL) in most women. In a phase 1 study, at a dose of 200 mg twice daily, elagolix led to nearly full suppression of E2 to levels observed during menses (less than 20 pg/mL) in most women …”
mentioning
confidence: 99%
“…In 2 large replicate phase 3 trials, both 150‐mg once‐daily and 200‐mg twice‐daily doses of elagolix were found to be safe and effective in improving both dysmenorrhea and nonmenstrual associated pelvic pain in women with endometriosis‐associated pain . The 2 doses of elagolix were associated with dose‐dependent hypoestrogenic adverse effects (eg, higher rates of hot flushes that were mostly mild or moderate, higher levels of serum lipids, and greater decreases from baseline in bone mineral density compared with placebo) …”
mentioning
confidence: 99%